An Exploration of Factors Affecting Speaking Difficulties among 2022 English Education Students in University - Wilda Utami; Erniwati Erniwati; Mukrim Mukrim; Abdul Kamaruddin (Journal of English Language and Education, 2026)
Speaking fluency is crucial for English competence, yet many English Education students still face speaking fluency difficulties despite completing speaking courses. This qualitative case study aimed to explore the forms of speaking fluency difficulties, their contributing factors, and students' coping strategies, involving 12 participants. Data were collected through open-ended questionnaires and semi-structured interviews. The findings revealed five forms of speaking fluency difficulties, influenced by thirteen factors and addressed through seven coping strategies. This research concludes that speaking fluency difficulties are multidimensional problems heavily rooted in linguistic deficits, highlighting the need for targeted instructional support to help students overcome these communication barriers.